Exclusive Dealing and Common Agency in International Markets - Horst Raff; Nicolas Schmitt (Center for Economic Studies and ifo Institute (CESifo), 2004)
This paper investigates the contractual choice between exclusive dealing and common agency in a simple international oligopoly model where products are sold through intermediaries. We find that when trade barriers are high domestic firms tend to adopt exclusive dealing contracts, whereas trade liberalization may lead firms to choose common agency. Irrespective of the level of trade barriers, the equilibrium contract adopted by each manufacturer is shown to decrease domestic welfare as compared to the other possible contract when products are close substitutes.
Keywords: 330